The Accuracy of Working Length Determination During Endodontic Retreatment - Chirila M.; Scarlatescu S. A.; Nistor C.C.; Moldoveanu G. F. (Romanian Journal of Oral Rehabilitation, 2011)
Aim. Endodontic retreatment requires complete removal of contents from the root canal and the orthograde endodontical approach of the whole system. Restoring access to the entire length of the canal will allow the action of the irrigation solution and the intracanal medicaments , thus facilitating the success of this approach. Methods. For this in vitro study were selected 30 maxillary anterior teeth, with fully formed apices, no root defects and intact crowns . The teeth were instrumented and filled by cold lateral condensation and then retreated, according to the protocol established for this experiment. After the endodontic retreatment the working length was determined using direct and electronic methods, the values being recorded and compared. Were used the following electronic apex locators: Root ZX(J. MoritaCorp.FGM, Kyoto, Japan), Element Diagnostic Unit(SybronEndo, SybronDental, Anaheim, CA, USA), ProPex(Dentslpy MailleferSwitzerland), i-Pex(NSK, NakanishiInc., Japan). Results. To validate the results, the measurements were recorded by two independent observers, all the values being placed in a statistical analysis program. The working lenghts were analyzed aiming to evaluate the apex locators’s performances , reported to the initials values and the specific endodontic retreatment implications. Accuracy of determinations was 96.6% (n29) for Morita, EDU93,3% (n28), 90% (n26) for Propex and 86,66% (n27) for I-pex. Conclusions. The apex-locators can be used successfully to determine the working length in endodontic retreatment. Determinations were not influenced by root canal sealer or gutta-percha. The file used to determine the working length is preferable to have an ISO size closer to apical constriction diameter, in order to obtain an accurate determination. Desing’s display and individual scale models may affect the accuracy of the results till the practitioner get used to an apex-locator.